Postgraduate Trainings in the Process of Professional Reform (Training and Practice : Journal of Educational Sciences, 2011)
In the school year 2010-2011 the Faculty of Pedagogy at Kaposvár University started a new professional course with the following title: Education of children with adaptional, learning and behavioral difficulties. The aim of the course is the professional development of those (functional) specialists who will be able to fulfill the identification, prevention and differentiated development of the children with these special treatment needs. The study presents the results of the questionnaire filled out by the teachers attending the first semester. The research tends to reveal those personal and institutional expectations that determined teachers to register for this course. The results of the research could be considered as feedback for the current course giving a gradeline how to enhance the efficiency of it and how to delineate the role of this course in the wide range of the courses.